A Note on the Names in Names. (1st September 2013) - Abel, Ernest Lawrence
Abstract : Names, the journal of the American Name Society, has been publishing articles on names since 1953, but, in the fifty-plus years of publication, Names has yet to publish any studies on the names of the authors who have contributed to the journal. This article examines the names of these contributors in terms of academic associations, prosody, and diversity.